Saídas de emergência: autobiografias e espiritualidades trans - Costa, Caio Jade Puosso Cardoso Gouveia (Sacrilegens, 2020)
This paper will present different religious and spiritual perspectives found in the autobiographical texts of Claudia Wonder, Roberta Close, Lorys Ádreon, Ruddy Pinho, Jorge Laffond and Jordhan Lessa. We will see how their sex/gender expressions are accepted or rejected by the religious systems of Brazilian society in their narratives. We will analyze how unique spiritualities are created as responses to the exclusions and formattings imposed by the religions. We will reflect on the desacralization of diverse sex/gender expressions as a strategy of social exclusion. Lastly, we will propose trans spiritualities as strategies of reintegration and re-sacralization of the beings into life.